Nature's fury extreme natural events : NCEA Level 1 - Anderson, Lois (Always learning, 2012)
"Nature's fury provides relevant case studies of historical and recent volcanic eruptions, tropical storms and earthquakes, including the eruption of Mt Pinatubo, Hurricane Katrina, Cyclone Percy, and the Haiti and Christchurch earthquakes. Accessible and easy to read, the book has many supporting illustrations and photographs. There are a variety of activities and exercises throughout that will give you valuable practice so you will develop the confidence you need to do well in your assessment."--Back cover